Update - Isabela Sattamini; Michael Purdy; Oliver Wainwright; The Update team; The Big Food Watch team; Peter Buffett; Stefanie Vandevijvere (World Nutrition, 2015)
Pesticides. The crisis in Brazil and worldwide Isabela Sattamini Gut microbial ecology. Secrets of the Yanomami Michael Purdy Expo Milan. Burning public money Oliver Wainwright Nourishment. GLiMMER glitter   Update team US consumers tweak food habits Big Food Watch team. Philanthrophic colonialism  Peter Buffett Visions Stefanie Vandevijvere